2013
DOI: 10.1039/c3ob41787e
|View full text |Cite
|
Sign up to set email alerts
|

ortho-Selective nucleophilic addition of amines to 3-borylbenzynes: synthesis of multisubstituted anilines by the triple role of the boryl group

Abstract: Nucleophilic addition of amines to 3-[(dan)boryl]benzynes (dan = 1,8-diaminonaphthalene) generated by a fluoride ion proceeded with high ortho-selectivity to give 2-borylaniline derivatives, under conditions that are tolerant to various functional groups. The (dan)boryl group of the adduct was hydrolyzed into a boronic acid under acidic conditions, which could further serve for various C-C, C-O, C-N, and C-H bond-formation reactions. The overall process provides a promising entry for preparing multisubstituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…In these cases, the reactive sites of the benzynes were completely controlled by the electron-withdrawing and electron-donating inductive effects of the C3-alkoxy and C3-boryl group, respectively. [68][69][70][71][72][73][74][75][76][77][78] The fluorination of 3-(tert-butyldimethylsilyl) benzyne 4f gave a mixture of meta-1f and ortho-1f in a 6.4 : 1 ratio under both batch and flow conditions (Entry 5). In this case, the regiochemistry is believed to be mainly controlled by the steric bulkiness of the C3-silyl group of 4f.…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, the reactive sites of the benzynes were completely controlled by the electron-withdrawing and electron-donating inductive effects of the C3-alkoxy and C3-boryl group, respectively. [68][69][70][71][72][73][74][75][76][77][78] The fluorination of 3-(tert-butyldimethylsilyl) benzyne 4f gave a mixture of meta-1f and ortho-1f in a 6.4 : 1 ratio under both batch and flow conditions (Entry 5). In this case, the regiochemistry is believed to be mainly controlled by the steric bulkiness of the C3-silyl group of 4f.…”
Section: Resultsmentioning
confidence: 99%
“…The distortion and electronic property strongly indicate that the C3-position of 3 a is more electrophilic than the C4-position, and the C4-position of 4 B is more nucleophilic than the C2-position (for details, see the Supporting Information). [18] Therefore, the delocalization of electrons between the C3-position of 3 a and the C4-position of 4 B, and that between the C4-position of 3 a and the C2-position of 4 B, may be the major driving force for the distal selective DA reaction. In a similar manner, the observed opposite proximal selectivity in the case of 3 f can be explained by the distortion [6i, 9f] and electronic properties [18] of 3 f (i.e., the C4-position of 3 f is more electrophilic).…”
Section: Resultsmentioning
confidence: 99%
“…[18] Therefore, the delocalization of electrons between the C3-position of 3 a and the C4-position of 4 B, and that between the C4-position of 3 a and the C2-position of 4 B, may be the major driving force for the distal selective DA reaction. In a similar manner, the observed opposite proximal selectivity in the case of 3 f can be explained by the distortion [6i, 9f] and electronic properties [18] of 3 f (i.e., the C4-position of 3 f is more electrophilic). The properties of 3 a and 3 b can be attributed to the electron-donating inductive effects of the Si and Sn atoms, respectively, and those of 3 f can be attributed to the electron-withdrawing inductive effect of the O atom (Allred-Rochow electronegativities: O, 3.5; C, 2.5; Si, 1.7; Sn, 1.7).…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] However, the requirement that the boronate be placed at the benzyne C3 position in these studies necessitated multistep preparation and revealed an incompatibility with fluoride in the absence of extremely robust protecting groups. [ 17c ] It also seemingly precluded use of the boronate prior to capture of the aryne and therefore the prospect of postfunctionalizing the aryne precursor. We reasoned that the remarkable functional-group tolerance of iridium-catalyzed C–H borylation[ 18 ] and its preference for the least sterically hindered position of simple arenes[ 19 ] would provide a direct way to introduce a B(pin) substituent selectively into precursors 1 , thereby preserving various R groups at C3, where they are known to influence aryne reactivity most profoundly.…”
mentioning
confidence: 99%